SPEAKING STRATEGIES USED BY INDONESIAN TERTIARY STUDENTS - Wawa Puja Prabawa (English Review: Journal of English Education, 2016)
Speaking is considered to be difficult thing, moreover English as a foreign language. Students' performance depends on their personalities. Students who have low participation in speaking activity in the classroom lose their opportunity to practice their speaking skill which may cause poor speaking skill and achievement. However, some of students are active in speaking activity in the classroom that leads them to have good skill and achievement in speaking. This study attempts to reveal: (1) speaking strategies used by Indonesian tertiary students in terms of speaking English and strategies to improve their speaking ability, and (2) to identify speaking strategies mostly used by the students when they speak English and improve their speaking ability. This study is a descriptive research since its purpose is to describe the Indonesian tertiary studentsâ€™ learning strategies in learning speaking English. The data from 15 tertiary students, who have good performance and achievement in speaking, from one of schools of higher education in Cimahi were collected using a 21 items questionnaire of a modified version of Strategy Inventory Language Learning (SILL) and 5 items interview questions. The result of the study revealed that some speaking strategies are used in terms of speaking English and improve speaking ability, namely cognitive, metacognitive and compensation strategy. In the type of speaking strategy that mostly used by the student in terms of speaking English is compensation strategy, while cognitive strategy was indicated as the mostly speaking strategies used by the Indonesian tertiary students in improving their speaking ability.Â  Considering to the study conducted, it is recommended to students that they should know what strategies that appropriate and can help them in learning speaking English. The students should be able to choose strategies they need in learning and analyze which strategies that give better effect on their own learning.Keywords: Speaking, strategy, speaking strategy, tertiary students